MENINGKATKAN BENEFIT PADA PROSES PENGURASAN AIR DARI KONTROL ELEKTRIK KE KONTROL PNEUMATIK, PADA SISTEM UDARA BERTEKANAN - Nugraha, Afitro Adam; Yohanes C. Sutama; Fauzan Arya Ramadani; Ade Susilo; Edi Widyartono, Andreas (LPPM Politeknik Astra, 2024)
In PT ADM Casting Plant, the use of compressed air is essential to operate several production machines that utilize pneumatic systems. The compressed air is sourced from the compressors owned by PT ADM Casting Plant. The compressed air must be dry and not wet or moist. If it is wet or moist, it can cause water to enter the air pipelines of the production machines and pose a corrosion risk due to condensation in the pneumatic lines of the production machines. Before entering the production machines, the compressed air must undergo several processes such as Suction-Storage-Drying. However, during the storage process, a significant amount of compressed air is wasted during the draining of condensed water accumulated in the Air Receiver Tank. The draining process still utilizes solenoid valves without any separator or divider between the condensed water and the compressed air, and it still relies on timing or time-based valve opening and closing as a benchmark. The wasted air results in difficulty achieving the desired air pressure produced by the compressor. Consequently, the compressor continues to operate to reach the predetermined air pressure. After analyzing the problem and available data, a solution was developed by replacing the solenoid valves with a Pneumatic No-Loss Drain. The purpose of this replacement is to serve as a separator between the condensed water and the compressed air during the draining process.